2015
DOI: 10.1016/j.mayocp.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Kidney Disease in American Indians: Potential Role of Sugar-Sweetened Beverages

Abstract: Since the early 20th century, a marked increase in obesity, diabetes, and chronic kidney disease has occurred in the American Indian population, especially the Pima Indians of the Southwest. Here, we review the current epidemic and attempt to identify remediable causes. A search was performed using PubMed and the search terms American Indian and obesity, American Indian and diabetes, American Indian and chronic kidney disease, and American Indian and sugar or fructose, Native American, Alaska Native, First Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 131 publications
0
23
0
Order By: Relevance
“…Natural selection could be responsible for more efficient energy storage, which results in a high prevalence of metabolic disorders [12,13]. Such significant changes in the prevalence of MetS could reflect the acculturation of a genetically susceptible population and the adoption of an obesogenic environment [19,20,24]. This assertion is supported by the observation that indigenous communities close to urban areas have a higher prevalence of metabolic disorders relative to communities with the same genetic background that remain isolated [19,24,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural selection could be responsible for more efficient energy storage, which results in a high prevalence of metabolic disorders [12,13]. Such significant changes in the prevalence of MetS could reflect the acculturation of a genetically susceptible population and the adoption of an obesogenic environment [19,20,24]. This assertion is supported by the observation that indigenous communities close to urban areas have a higher prevalence of metabolic disorders relative to communities with the same genetic background that remain isolated [19,24,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the Mexican population is Mestizo with a strong Amerindian component (56%) [15], and an estimated 14.9% of the Mexican population comprises indigenous people distributed over 68 ethnic groups [16,17]. Although many of these indigenous populations have retained their genetic backgrounds, native languages, and socioeconomic structures over the centuries [16,18], over the last few decades they have experienced dramatic changes in their lifestyles, primarily with regard to excessive energy intake and a sedentary lifestyle [19,20]. Parallel with this progressive change, an increase in the prevalence of metabolic diseases has been observed [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of SSB is closely linked to socioeconomic class, with poorer communities displaying relatively higher intakes compared with their more affluent counterparts. For example, the Native American Indian population exhibits a relatively high prevalence of obesity and T2DM, and here it was reported that a significant percentage of Navajo girls and boys consumed SSBs (86% and 93%, respectively) [ 66 ]. Together these studies show that SSB intake not only is detrimental to the adult population but extends to adolescents as well and that its effects may vary depending on ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups, such as male adolescents (aged 12‐19 years), consumed 12% of their overall energy from these drinks . The highest intake of sugar‐sweetened beverages occurs in adolescents, young adults in their 20s, individuals with a lower socioeconomic status , and certain ethnically defined populations, including African American , Hispanic , American Indian and Alaskan Native , and Pacific peoples .…”
Section: Impact Of Liquid Sugars In Human Dietmentioning
confidence: 99%